Ronald Egan's Research on the History of the Northern Song Ci Poetry from a Gender Perspective - Yanping, Chen (Social sciences in China, 2023)
Ronald C. Egan, a renowned American sinologist, is best known for his accurate English translations, exquisite readings, and innovative perspectives on the aesthetic ideas and pursuits of ci poets such as Ouyang Xiu, Su Shi, and Li Qingzhao, as well as the scholar-official group of the Northern Song dynasty. However, through his longitudinal study of specific ci poets, he also shows a unique understanding of the development and evolution of ci lyric poetry in the Northern Song. An integrated analysis of Egan's scattered articles on Northern Song ci poetry indicates that gender is key to his understanding of the evolution of ci in the Northern Song. On this basis, Egan has conducted in-depth research on three aspects: the gender perspective of the lyrical protagonists described by ci poets; changes in the form, content, and patterns of writing ci poetry; and new phenomena in ci criticism. His research further enriches the details of the evolution of Northern Song ci poetry and expands its historical research horizon.